2007
DOI: 10.2753/mis0742-1222240302
|View full text |Cite
|
Sign up to set email alerts
|

A Design Science Research Methodology for Information Systems Research

Abstract: ABSTRACT:The paper motivates, presents, demonstrates in use, and evaluates a methodology for conducting design science (DS) research in information systems. DS is of importance in a discipline oriented to the creation of successful artifacts. Several IS researchers have pioneered DS research in IS, yet over the last 15 years little DS research has been done within the discipline. The lack of a methodology to serve as a commonly accepted framework for DS research and of a template for its presentation may have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
3,541
1
284

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 4,880 publications
(3,837 citation statements)
references
References 42 publications
11
3,541
1
284
Order By: Relevance
“…To conduct this research we have followed design science principles as suggested by Hevner et al (2004) and, in particular, we have applied the design science research methodology (DSRM) (Peffers et al 2007) as follows: Problem identification and motivation phase : In this phase, we reviewed both research proposals related to our research question, i.e., responsibility management applied to executable business processes, and how this is currently applied in industry. Table 3 collects those that take into consideration more than one type of responsibility.…”
Section: Motivation and Research Methodsmentioning
confidence: 99%
“…To conduct this research we have followed design science principles as suggested by Hevner et al (2004) and, in particular, we have applied the design science research methodology (DSRM) (Peffers et al 2007) as follows: Problem identification and motivation phase : In this phase, we reviewed both research proposals related to our research question, i.e., responsibility management applied to executable business processes, and how this is currently applied in industry. Table 3 collects those that take into consideration more than one type of responsibility.…”
Section: Motivation and Research Methodsmentioning
confidence: 99%
“…The four main steps of this study were [19]: problem identification, definition of objectives of the artifact, design and development of the artifact, and evaluation of the artifact. The authors demonstrated in a laboratory the solution's contribution to the organizational learning field and collected feedback for further development.…”
Section: Methodsologymentioning
confidence: 99%
“…This stage provides additional support to the viability of the proposed artifact as a solution to the identified research problem. In this article demonstration serves the role of evaluation by offering an example instantiation and application of the artifact [5]. Such approach is applicable in validation, especially when repeatedly applying the artifact and measuring its influence is practically difficult, which is a common problem to all IS research [1].…”
Section: Research Approachmentioning
confidence: 99%
“…The research presented in this article describes the development of one such organizational artifact: a quality-driven and model-driven IS integration methodology. The artifact is developed following the six stages of Design Science Research Methodology (DSRM) [5]. This section describes how the stages were followed during the course of this research.…”
Section: Research Approachmentioning
confidence: 99%